2014
DOI: 10.1002/ange.201408732
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten‐Catalyzed Regio‐ and Enantioselective Aminolysis of trans‐2,3‐Epoxy Alcohols: An Entry to Virtually Enantiopure Amino Alcohols

Abstract: The first catalytic enantioselective aminolysis of trans‐2,3‐epoxy alcohols has been accomplished. This stereospecific ring‐opening process was efficiently promoted by a tungsten/bis(hydroxamic acid) catalytic system, furnishing various anti‐3‐amino‐1,2‐diols with excellent regiocontrol and high enantioselectivities (up to 95 % ee). Moreover, virtually enantiopure 3‐amino‐1,2‐diols could be obtained by the sequential combination of two reactions that both involve the use of a chiral catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In this context, Yamamoto reported in 2014 a catalytic regioselective and stereospecific ring opening of 2,3epoxy alcohols promoted by achiral tungsten salts. [51] Then, they described the enantioselective aminolysis of 2,3-epoxy alcohols with various amines as the nucleophiles using the tungsten-bishydroxamic acid catalytic system , [52] which can perform both the epoxidation and the ring-opening reaction thus providing the enantiopure 3-amino-1,2-diols. The sub- strate scope showed that all the reactions proceeded at 55 °C in the presence of a W-BHA catalytic system (2.5 or 5 mol%), with enantioselectivities ranging from 40 to 95 %.…”
Section: Regio and Enantioselective Aminolysis Of Trans-23-epoxy Alco...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Yamamoto reported in 2014 a catalytic regioselective and stereospecific ring opening of 2,3epoxy alcohols promoted by achiral tungsten salts. [51] Then, they described the enantioselective aminolysis of 2,3-epoxy alcohols with various amines as the nucleophiles using the tungsten-bishydroxamic acid catalytic system , [52] which can perform both the epoxidation and the ring-opening reaction thus providing the enantiopure 3-amino-1,2-diols. The sub- strate scope showed that all the reactions proceeded at 55 °C in the presence of a W-BHA catalytic system (2.5 or 5 mol%), with enantioselectivities ranging from 40 to 95 %.…”
Section: Regio and Enantioselective Aminolysis Of Trans-23-epoxy Alco...mentioning
confidence: 99%
“…The epoxidation followed by the ring‐opening reaction was also studied, and this strategy's implementation allows optically pure amino alcohols in up to 99.8 % enantiomeric excess (Scheme 38). [52] …”
Section: Second‐generation Bishydroxamic Acid (Bha)mentioning
confidence: 99%
“…Sharpless) epoxidation [46][47][48][49][50][51][52] followed by C-3 regioselective ringopening of 2,3-epoxy alcohols with amines. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] In the last decade, a metal-and solvent-free protocol, 69 involving C-3 selective ring-opening of 2,3-epoxy alcohols with amines catalysed by W-salts, 70 b-cyclodextrin, 66 MgCl 2 , 71 or the tungsten/ bis(hydroxamic acid) system 72 as well as a two-step combined epoxidation/ring-opening methodology 73 were shown to generate virtually enantiopure functionalised 3-amino-1,2diols. The ring-opening of chiral epoxy alcohols with nucleophiles [74][75][76][77][78][79][80][81][82] provides direct access to versatile chiral building blocks for the synthesis of natural products and synthetic analogues with promising biological activities, 83,84 such as cardiovascular, 85 antibacterial 86,87 and sedative effects.…”
Section: Introductionmentioning
confidence: 99%